Prótese overdenture: Sistema O'ring - Chamas, Jamil [UNESP] (2015)
Overdenture is a denture that utilizing retentive supports for increase stability and retention in oral cavity. The tooth-supported overdenture require dental elements with root canal therapy and good periodontal support. The aim of this study is to report the confection of a maxillary tooth-supported overdenture associated with mandibular denture and your clinical steps. This rehabilitation promotes the patient's adaptation the new condition, since the use of conventional dentures may cause discomfort due to lack of retention and stability. The preservation of dental elements promotes bone maintenance and forthcoming decision of the patient in the installation of dental implants that can choose implant-retained or implant-supported prosthesis. Patient was satisfied with aesthetic and functional result after installation of prosthesis